Pengaruh Metaverse Marketing terhadap Consumer Perception dengan Roblox Experience sebagai Variabel Mediasi pada Pengguna Roblox Indonesia yang Terpapar Kampanye Adidas - Muhammad Elfan Hernantyo; Catharina Aprilia Hellyani; Santi Widyaningrum; Sahala Manalu; Teofilus Karnalim (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
Digital transformation encourages global brands to adopt marketing strategies within virtual environments to engage young consumers. This study analyzes the impact of metaverse marketing on consumer perception, with Roblox experience as a mediating variable among Roblox platform users in Indonesia exposed to the Adidas campaign. The research is backgrounded by the growth of the creative fashion sector and the shift toward immersive brand experiences. The methodology employs a quantitative approach utilizing Partial Least Squares–Structural Equation Modeling (PLS-SEM). Primary data were gathered via online questionnaires from 103 Roblox users in Indonesia selected through purposive sampling. All constructs were evaluated using reflective indicators on a Likert scale and analyzed with SmartPLS software. The structural model assessment reveals that metaverse marketing does not exert a significant direct effect on consumer perception. Conversely, metaverse marketing demonstrates a strong positive and significant impact on Roblox experience, which subsequently enhances consumer perception. Furthermore, indirect effect testing confirms that Roblox experience fully mediates the relationship. In conclusion, virtual marketing stimuli cannot automatically generate positive evaluations; campaigns must be converted into interactive experiences to optimally construct consumer perception.